Legal Review of Liability for Material Losses Resulting from Adverse Events Following Immunization (AEFI) in Non-Mandatory Immunizations - Roy Ivan Fidelis Hasugian; Nin Yasmine Lisasih (International Journal of Science and Environment (IJSE), 2026)
This research is motivated by the vulnerability of patients to material losses resulting from Adverse Events Following Immunization (AEFI), in circumstances where no automatic compensation scheme is available. This research aims to analyze hospital liability and legal protection for victims of AEFI. Employing a normative–empirical legal research method (socio-legal research) with statutory, conceptual, and case approaches, this research conducts observations at five healthcare facilities in the Bekasi region and analyzes relevant regulatory frameworks. The first part of the discussion demonstrates that, based on the principle of commutative justice and the doctrine of vicarious liability (Article 1367 of the Indonesian Civil Code), hospitals bear full responsibility for the negligence of their medical personnel; however, empirically, such liability is often reduced to mere administrative procedures. The second part of the discussion identifies defects in preventive legal protection, where healthcare facilities include exoneration clauses (disclaimers of liability) in informed consent forms that violate Article 18 of the Consumer Protection Law, as well as weaknesses in repressive legal protection, which is limited to patient referrals without the assumption of treatment costs. In conclusion, hospitals are obligated to provide restitution in integral, including full coverage of medical treatment costs for victims resulting from procedural errors. The author recommends that hospitals eliminate illegal standard clauses and establish healthcare cost guarantee schemes as a manifestation of product liability and professional responsibility.